2010
DOI: 10.1097/prs.0b013e3181e5f844
|View full text |Cite
|
Sign up to set email alerts
|

The Single Dominant Medial Row Perforator DIEP Flap in Breast Reconstruction: Three-Dimensional Perforasome and Clinical Results

Abstract: The single dominant medial row perforator has a maximal vascularity in zones I and II, and less in zones III an IV. The authors recommend that half of zone III and all of zone IV be discarded to avoid the risks of partial flap loss and fat necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 12 publications
0
64
1
1
Order By: Relevance
“…Among these, 15 presented data for msTRAM, DIEP, or SIEA flaps, and 8 of these 15 described complication rates for both obese and nonobese patients and thus were considered for estimating the RR 20,21,23,[25][26][27][28][29] (Table 1). Four studies presented data only for DIEP flaps 20,21,28,29 ; 3, for msTRAM and DIEP flaps [25][26][27] ; and 1, for msTRAM, DIEP, and SIEA flaps.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among these, 15 presented data for msTRAM, DIEP, or SIEA flaps, and 8 of these 15 described complication rates for both obese and nonobese patients and thus were considered for estimating the RR 20,21,23,[25][26][27][28][29] (Table 1). Four studies presented data only for DIEP flaps 20,21,28,29 ; 3, for msTRAM and DIEP flaps [25][26][27] ; and 1, for msTRAM, DIEP, and SIEA flaps.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…41 Most authors considered skin loss between 10 and 20 percent 17,18,20,42-45 as their cutoff for inclusion, although some authors labeled flaps with less than 5 percent skin loss as "partial necrosis," 46,47 and others categorized skin loss greater than 20 percent as "partial necrosis." 19,35,39,48 Fat necrosis had a range of definitions, including (1) absolute size (lumps >0.5 cm, 49 >1 cm, 6,25,39,50 >2 cm, 15,40,51 >3 cm 16 confirmed not to be malignant recurrence) detected clinically or by ultrasound 49,52,53 and/or mammography 46,54 , (2) proportion of volume of flap 18,43 , and (3) incidence of secondary operations to address fat necrosis.. 21,22,[55][56][57] Other authors chose to describe necrosis as "minor," 58 "minimal," 59 or "limited." 60 Another variable in fat necrosis reporting was the time frame-many authors reported detection rates at 2 39 to 3 6,15 months after the initial reconstruction, but others reported rates at 1 month 41 or even 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…24 The goal of flap design should be to maximize the blood flow to the central portion of the flap through the pedicle to make sure all parts of the flap are properly perfused. 19 To do so, the dominant perforator must be as close to the center of the flap as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Including the dominant perforator will decrease the resistance to blood flow, provide better vascular supply, and increase chances of flap viability and decrease blood flow related complications. 19 The current DIEP flap design uses either medial or lateral branches of the deep inferior epigastric artery that penetrate the rectus muscle and its sheath to supply the overlying adipose tissue. An incision is made at or directly above the umbilicus and continues almost to the anterior superior iliac crest.…”
Section: Discussionmentioning
confidence: 99%